Strategies for Customer Relationship Management Focused on Loyalty - J. Vasco; C. Guerra; F. Favicela; X. Granizo (ESPOCH Congresses)
This research examined the customer loyalty process through relational marketing, using Customer Relationship Management (CRM) strategies. A market study was conducted to analyze the current client management approaches. A survey of customers of the company was carried out to investigate what they perceived were important factors influencing their relationship with the organization and determining efficient communication. The study focused on the design of CRM and relational marketing strategies, in order to create tools to improve communication and interaction with the client, so as to help understand customer demands and achieve loyalty. A formal methodology was described for developing and implementing a CRM system that integrates aspects such as defining a customer strategy, re-engineering customer-oriented business processes, human resources management, the computer system, and management of change and continuous improvement.